The expression of LEP, LEPR, IGF1 and IL10 in obesity and the relationship with microRNAs. - Renata Viesti A Collares; Wilson Salgado; Daniela Pretti da Cunha Tirapelli; José Sebastião dos Santos (PLoS ONE)
Obesity is a multifactorial disease, with epigenetic alterations. Have been described modifications in the expression of some microRNAs, and some proteins related to obesity. The objective was to determine and correlate, in obese patients, the gene expression of LEP, LEPR, IGF1, IL10 and of miR-27a, miR-27b, miR-143 and miR-145. RNA was extracted from biopsies of subcutaneous fat, liver and visceral fat of 15 obese subjects submitted to bariatric surgery and of 15 non-obese subjects submitted to cholecystectomy for cDNA synthesis and for RT-PCR. The microRNAs were chosen using the TargetScan software. An increased expression of LEP and IGF1 was detected in the subcutaneous fat of the obese group compared to control, while the expression of IGF1 was higher in the control group than in the obese one. MiRNA-27a had a higher expression in the omentum of the obese patients and there was also a correlation in the expression of miRNA-145 and LEPR in the omentum of this group.